Arte, loucura, terapias - uma reflexão contemporânea (o Hospital de Clínicas da Universidade Federal de Uberlândia e as oficinas terapêuticas) - Dantas, Vânia de Freitas (2006)
This research is about the return of the acceptance of the insanity speech, which appears in activities in general, as the social-recreative , occupational, therapeutical, familiar, productive and artistic ones, from changes in the insanity understanding form and from the action forms of the insanity intitutions permeated by the action of the State, through the law. Considering the insanity not only as an organic affection, but mainly as a result of social interactions, it´s nothing more logical than treat it ( by the therapeutical, which involves the clinic and the disease notion or the behaviour deviation) or accompain it ( by the knowledge of the human science) through the ways that would focus on the social relationships in order to rescue the subject interaction potential. So, we were initially guided by the insanity epistemological field as deviation of the comportamental norm, according to Focault and Sasz, either by environmental or organic delinking, and lead, in a sociology, for a notion of the historical construction of the individual fighting for his surpassing and composing of an individuality/ identity. The first step to such surpressing is the construction of the authentic individual, through the acceptance of the expressivity of the mad one by the society and by the medical knowledge in the therapeutical workshops, specially the plastic art ones.The acceptance of the insanity speach was studied through the experience with Therapeutical Workshops in the psicholycal clinic of UFU in the period of 1991 - 1998 , identifying the involved speeches in this subjectivity experiment of the insanity subject, examinig for this reason the context in which the psychiatrist medical knowledge is placed, the voice of the State through the rules about mental health , the psychologist scientific speech, from the philosophy and the activity of the municipal, state and federal mental health net, that established the practice of workshops through the Psycho-Social Attention Centres, CAPs, which integrate the attention net for the mental health services users. We tried to meet insanity and art, object and therapeutical form from a humanization understanding of the institutions which deal with human beings